Host Range of Psilenchus De Man, 1921 among Mostly Grown Crops in Kashmir and its Respective Population Build-up - Sheikh, Javaid Hassan (Asian Journal of Biological and Life Sciences, 2020)
As a part of the project in 2019-2020, a general survey was conducted in all the ten districts of the Kashmir valley to investigate the occurrence of various plant parasitic nematodes on most commonly grown crops. Psilenchus spp. was isolated from Solanum tuberosum, Brassica oleracea, Capsicum frustscens and Spinacia oleracea with the varied population build-up. Psilenchus spp. was met with a varied occurrence parameters of 86.6 % of absolute frequency and 26% of relative prominence value on Solanum tuberosum. 76.6% of absolute frequency of this nematode was met on Brassica oleracea with 15.7% of relative prominence value. Spinacia oleracea was met with a varied occurrence parameters of 86.6 % of absolute frequency and 26% of relative prominence value of the Psilenchus spp. In all the samples of Capsicum frustscens screened the nematode was met with 100% absolute frequency making the crop comparatively one among highly vulnerable hosts.
Keywords: Brassica oleracea; Kashmir; Psilenchus; Solanum tuberosum; Nematode